Cis and trans determinants of epigenetic silencing by Polycomb repressive complex 2 in Arabidopsis - Xiao, Jun; Jin, Run; Yu, Xiang; Shen, Max; Wagner, John D; Pai, Armaan; Song, Claire; Zhuang, Michael; Klasfeld, Samantha; He, Chongsheng; Santos, Alexandre M; Helliwell, Chris; et al. (Nature genetics, 2017)
Doris Wagner and colleagues define Polycomb response elements (PREs) that direct the placement of Polycomb repressive complex 2 (PRC2) at developmental genes in Arabidopsis . They identify transcription factor families that bind to PREs, physically interact with and recruit PRC2, and are required for gene silencing in vivo . Disruption of gene silencing by Polycomb protein complexes leads to homeotic transformations and altered developmental-phase identity in plants 1 , 2 , 3 , 4 , 5 . Here we define short genomic fragments, known as Polycomb response elements (PREs), that direct Polycomb repressive complex 2 (PRC2) placement at developmental genes regulated by silencing in Arabidopsis thaliana . We identify transcription factor families that bind to these PREs, colocalize with PRC2 on chromatin, physically interact with and recruit PRC2, and are required for PRC2-mediated gene silencing in vivo . Two of the cis sequence motifs enriched in the PREs are cognate binding sites for the identified transcription factors and are necessary and sufficient for PRE activity. Thus PRC2 recruitment in Arabidopsis relies in large part on binding of trans -acting factors to cis -localized DNA sequence motifs.